(untitled) (Global Journal of Science Frontier Research, 2015)
Smoked Clarias gariepinus from four major markets in the southwest, Nigeria were analyzed. The aim was to evaluate the nutritional values of the fish sold at the different markets. The results of the analyses showed that the nutritional values of the smoked fish are of good standard but nutritional and mineral compositions varied from market to market. The moisture content, protein, fat, fibre, ash and carbohydrate contents from the markets were in the range of 9.63 to 10.27%, 53.77 to 54.77%, 11.77 to 13.13%, 6.87 to 8.00%, 0.0 to 0.07% and 15.40 to 16.17% respectively. The range of the mineral compositions was 10.13 to 12.17mg/100g, 0.33 to 0.50mg/100g, 28.33 to 46.67mg/100g, 353.33 to 388.33mg/100g, 22.33 to 33.33mg/100g, and 271.67 to 305.00mg/100g for iron, zinc, magnesium, calcium, potassium and phosphorus respectively. Ascorbic acid, thiamine, niacin and riboflavin contents of the fish were in range of 0.17 to 0.27mg/100g, 0.05 to 0.07mg/100g, 0.24 to 0.28mg/100g, and 0.05 to 0.08mg/100g respectively.